2011
DOI: 10.1227/neu.0b013e31820783d5
|View full text |Cite
|
Sign up to set email alerts
|

A New Metric for Detecting Change in Slowly Evolving Brain Tumors: Validation in Meningioma Patients

Abstract: Background Change detection is a critical component in the diagnosis and monitoring of many slowly evolving pathologies. Objective This article describes a semi-automatic monitoring approach using longitudinal medical images. We test the method on brain scans of meningioma patients, which experts found difficult to monitor as the tumor evolution is very slow and may be obscured by artifacts related to image acquisition. Methods We describe a semi-automatic procedure targeted towards identifying difficult-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Discussion [4] reported that an expert wrongly classified all cases with 1% artificial lesion growth, and only achieved an accuracy of 20% for cases with 5% growth. The same expert, however, correctly classified all cases with a 22% growth.…”
Section: Comparison With Qe Values From Sommentioning
confidence: 97%
See 1 more Smart Citation
“…Discussion [4] reported that an expert wrongly classified all cases with 1% artificial lesion growth, and only achieved an accuracy of 20% for cases with 5% growth. The same expert, however, correctly classified all cases with a 22% growth.…”
Section: Comparison With Qe Values From Sommentioning
confidence: 97%
“…This is especially true for scans taken at relatively short intervals (less than a year). Visual inspection often misses the slow evolution because the change may be obscured by variations in body position, slice position, or intensity profile between scans, as noted by [4]. In some cases, the change can be too small to be noticed, leaving a patient to fate.…”
Section: Comparison With Qe Values From Sommentioning
confidence: 99%
“…One of the fields that may particularly benefit from computer-aided methods is the assessment of changes in a patient's tumor burden especially when the tumor evolution is slow. This issue has recently been addressed with the development of a computerassisted semi-automated method applied on slow-growing meningiomas [14]. A benefit of a 3D volumetric approach compared to 2D-based volume analysis has recently been Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of longitudinal changes in brain MRI scans has gained much attention in recent years. [15][16][17][18][19][20][21][22][23][24] Some of these methods register follow-up MR scans and analyze the changes between the scans. Patriarche and Erickson 22 present a graylevel based change detection.…”
Section: Introductionmentioning
confidence: 99%
“…Chitphakdithai et al 16 simultaneously estimate the registration parameters and label the changes between two consecutive brain scans to track metastatic brain tumors. Pohl et al 23 present a pipeline method to segment a tumor in a set of longitudinal scans based on user guided segmentation of the first scan. Menze et al 10 and Konukoglu et al 25 present approaches for modeling tumor growth in longitudinal images based on a reaction-diffusion framework.…”
Section: Introductionmentioning
confidence: 99%